Simulation of human diving and splashing fluids - O'Brien, J. F.; Wooten, W. L.; Hodgins, J. K. (1996)
Physically based simulation of 10 meter platform dives from the initial stance of a human diver to the splash at water entry. A dynamic model and control system are used to generate the motion of the diver. The dynamics of incompressible fluids and particle systems are combined to produce the splash.